Health Literacy and its Related Factors in Infant's Mothers - Seyyed Hamid Reza Fallah Morteza-Nejad; MohammadHossein YektaKooshali; Sadegh MoshtaghiKojal; Zohreh Salmalian; Aboozar Ramezani; Mohammad EsmaeilpourBandboni (Hamadan University of Medical Sciences, 2019)
Aims: Health literacy includes not only the ability to read but also a set of complicated skills. Health literacy is important for understanding health messages and choosing the appropriate decision. The aim of this study was to determine the level of health literacy of mothers with infants who referred to urban health centers of Guilan. Instruments & Methods: This cross-sectional descriptive-analytical study was carried out on 253 mothers with infants who referred to urban health centers covered by the Guilan University of Medical Sciences for receiving routine care in 2018. These subjects were selected using random sampling method. For data collection, the standard information literacy questionnaire (HELIA) was distributed among eligible mothers according to inclusion criteria. Collected data were analyzed by SPSS 19 software using Spearman Correlation, Kruskal-Wallis and Mann-Whitney tests. Findings: The mean score of maternal health literacy was 72.33±13.04. There was a significant relationship between the health literacy and maternal education level and occupational status (p<0.05). Conclusion: The level of health literacy in mothers with infants is desirable, but it depends on various factors and can change over time.